Frequent IDH2 R172 mutations in undifferentiated and poorly‐differentiated sinonasal carcinomas. Issue 4 (9th June 2017) - Dogan, Snjezana; Chute, Deborah J; Xu, Bin; Ptashkin, Ryan N; Chandramohan, Raghu; Casanova‐Murphy, Jacklyn; Nafa, Khedoudja; Bishop, Justin A; Chiosea, Simion I; Stelow, Edward B; Ganly, Ian; Pfister, David G; et al.
Abstract: Sinonasal undifferentiated carcinoma (SNUC) is a high‐grade malignancy with limited treatment options and poor outcome. A morphological spectrum of 47 sinonasal tumours including 17 (36.2%) SNUCs was analysed at genomic level. Thirty carcinomas (cohort 1) were subjected to a hybridization exon‐capture next‐generation sequencing assay (MSK‐IMPACT TM ) to interrogate somatic variants in 279 or 410 cancer‐related genes. Seventeen sinonasal tumours (cohort 2) were examined only for the presence of IDH1/2 exon 4 mutations by Sanger sequencing. IDH2 R172 single nucleotide variants were overall detected in 14 (82.4%) SNUCs, in two (20%) poorly‐differentiated carcinomas with glandular/acinar differentiation, and in one of two high‐grade neuroendocrine carcinomas, large cell type (HGNECs). No IDH2 mutation was detected in any of five olfactory neuroblastomas or in any of five SMARCB1 ‐deficient carcinomas. Among 12 IDH2 ‐mutated cases in cohort 1, five (41.7%) harboured co‐existing TP53 mutations, four (33.3%) CDKN2A/2B loss‐of‐function alterations, four (33.3%) MYC amplification, and three (25%) had concurrent SETD2 mutations. AKT1 E17K and KIT D816V hotspot variants were each detected in one IDH2 ‐mutated SNUC . The vast majority of SNUCs and variable proportions of other poorly‐differentiated sinonasal carcinomas may be amenable to IDH2‐targeted therapy. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.